Systematic review and meta-analysis of interventions relevant for young offenders with mood disorders, anxiety disorders, or self-harm - Townsend, Ellen; Walker, Dawn-Marie; Sargeant, Sally; Vostanis, Panos; Hawton, Keith; Stocker, Olivia; Sithole, Jabulani (Elsevier, 2009)
Background: Mood and anxiety disorders, and problems with self harm are significant and serious issues that are common in young people in the Criminal Justice System. Aims: To examine whether interventions relevant to young offenders with mood or anxiety disorders, or problems with self harm are effective. Method: Systematic review and meta-analysis of data from randomised controlled trials relevant to young offenders experiencing these problems. Results: An exhaustive search of the worldwide literature (published and unpublished)yielded 10 studies suitable for inclusion in this review. Meta-analysis of data from three studies (with a total population of 171 individuals) revealed that group-based Cognitive Behaviour Therapy (CBT) may help to reduce symptoms of depression in young offenders. Conclusions: These preliminary findings suggest that group-based CBT may be useful for young offenders with such mental health problems, but larger high quality RCTs are now needed to bolster the evidence-base.